Effect of Vitamin D Supplementation on Irisin, Telomerase, Klotho, and Tumor Necrosis Factor-alpha (TNF-α) in Elderly: A Quasi-Experimental Study - Diniwati Mukhtar; Nunung Ainur Rahmah; Sri Wuryanti; Himmi Marsiati; Desi Ariyani Haddad; Sabarina Elfrida Manik; Linda Weni; Bistamy Muhammad Nursabur; Andrea Ivana Allicia Hutabarat; Switania Putri Puspita (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Vitamin D plays a crucial role in aging by regulating mitochondrial function, inflammation, oxidative stress, and telomere stability. Vitamin D deficiency is common among the elderly and is linked to accelerated aging. Biomarkers such as irisin, telomerase, klotho, and tumor necrosis factor-alpha (TNF-α) are associated with aging processes. This study aimed to evaluate the effect of vitamin D supplementation on these biomarkers in elderly individuals.Methods: This quasi-experimental pretest-posttest study was conducted in Kadugadung Village, Banten, Indonesia from Maret to September 2024. A total of 47 healthy elderly individuals (≥60 years) were recruited using purposive sampling. The treatment group (n=25) received 800 IU/day of vitamin D for 20 days, whereas the control group (n=22) received none. Blood samples were collected before and after the intervention to measure serum irisin, telomerase activity, klotho, and TNF-α. Baseline variables included body mass index (BMI), blood pressure, hemoglobin, hematocrit, blood glucose, cholesterol, and uric acid. Data were analyzed using paired and independent statistical tests.Results: Vitamin D supplementation significantly increased serum irisin levels (p=0.016), meanwhile no significant changes were observed in telomerase activity (p=0.128), klotho (p=0.819), or TNF-α (p=0.098). In the treatment group, blood glucose was correlated positively with TNF-α (r=0.423, p<0.05), whereas cholesterol was correlated negatively with TNF-α (r=-0.51, p<0.01). Furthermore, telomerase activity was correlated positively with irisin (r=0.348, p<0.05)Conclusion: Vitamin D supplementation at 800 IU/day significantly enhances serum irisin, but does not affect telomerase, klotho, or TNF-α. These findings suggest a potential role of vitamin D in modulating aging-related biomarkers. Correction Notice: This article has been corrected. See the Erratum published in Althea Medical Journal, Volume 12, Number 4 (2025).